TSA-seq reveals a largely conserved genome organization relative to nuclear speckles with small position changes tightly correlated with gene expression changes - Zhang, Liguo; Zhang, Yang; Chen, Yu; Gholamalamdari, Omid; Wang, Yuchuan; Ma, Jian; Belmont, Andrew S. (Genome Research, 2021)
TSA-seq mapping suggests that gene distance to nuclear speckles is more deterministic and predictive of gene expression levels than gene radial positioning. Gene expression correlates inversely with distance to nuclear speckles, with chromosome regions of unusually high expression located at the apex of chromosome loops protruding from the nuclear periphery into the interior. Genomic distances to the nearest lamina-associated domain are larger for loop apexes mapping closest to nuclear speckles, suggesting the possibility of conservation of speckle-associated regions. To facilitate comparison of genome organization by TSA-seq, we reduced required cell numbers 10- to 20-fold for TSA-seq by deliberately saturating protein-labeling while preserving distance mapping by the still unsaturated DNA-labeling. Only ∼10% of the genome shows statistically significant shifts in relative nuclear speckle distances in pair-wise comparisons between human cell lines (H1, HFF, HCT116, K562); however, these moderate shifts in nuclear speckle distances tightly correlate with changes in cell type–specific gene expression. Similarly, half of heat shock-induced gene loci already preposition very close to nuclear speckles, with the remaining positioned near or at intermediate distance (HSPH1) to nuclear speckles but shifting even closer with transcriptional induction. Speckle association together with chromatin decondensation correlates with expression amplification upon HSPH1 activation. Our results demonstrate a largely “hardwired” genome organization with specific genes moving small mean distances relative to speckles during cell differentiation or a physiological transition, suggesting an important role of nuclear speckles in gene expression regulation.
10.1101/gr.266239.120